Early Marriage According To Islamic Law - Hidayati, Delti; Assa'diah, Nur Halimah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2021)
Marriage is a form of worship, this is in line with the definition of marriage in the Islamic Law Compilation which reads; marriage is a very strong mitsaqan ghalizhan contract to obey Allah's commands and carry out it is worship. Religion and state also provide rules for marriage, especially at the age of the prospective husband and wife, so that it can be considered mature, with the aim of achieving sakinah mawaddah warahmah. However, there were several cases of underage marriage in Indonesia. And it is in the background of many factors and their respective goals. Among the factors are wanting to maintain religion, honor and achieve happiness and welfare. Such as the case of early marriage in the Tanjung Morawa area in Bangun Sari Village. They decided to get married because the candidates who came were people of good religion and morals, so that the married life they live is blessed according to their hopes and dreams.